Leiomyosarcoma in the Nasopharynx: MR Imaging Findings - Kuo, R.; Huang, J.K.; Lee, K.S.; Chen, B.F.; Yang, F.S. (American Journal of Neuroradiology, 2007)
SUMMARY: The MR imaging findings of a leiomyosarcoma arising from the nasopharynx are presented. To our knowledge, this is the first MR imaging description of this entity.